2013
DOI: 10.4018/ijcallt.2013070103
|View full text |Cite
|
Sign up to set email alerts
|

Online Communities of Practice and Second Language Phonological Acquisition

Abstract: Second language (L2) researchers have long recognized the potential benefits of incorporating pronunciation instruction in language curricula (among others), and have investigated a variety of training types both in and out of the classroom, meeting with mixed successes. Likewise, technological advances provide educators with new tools that foster collaboration among learners and encourage the crucial processes of input, interaction and output (Long, 1996; Pica, 1994; Swain, 1985) beyond the walls of the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Although oral recordings projects have been mentioned in the L2 phonetics instructional literature as a recommended element of pronunciation teaching (Correa & Grim, 2014) or included as part of the study (Counselman, 2015;Elliott, 1995), they have not been the primary focus of many studies. Only three studies to my knowledge have focused on oral recordings projects, Ducate and Lomicka (2009), Lord (2008) and Lord and Harrington (2013). These three studies tested intermediate L2 learners.…”
Section: Oral Recordings Projects and Learner Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although oral recordings projects have been mentioned in the L2 phonetics instructional literature as a recommended element of pronunciation teaching (Correa & Grim, 2014) or included as part of the study (Counselman, 2015;Elliott, 1995), they have not been the primary focus of many studies. Only three studies to my knowledge have focused on oral recordings projects, Ducate and Lomicka (2009), Lord (2008) and Lord and Harrington (2013). These three studies tested intermediate L2 learners.…”
Section: Oral Recordings Projects and Learner Attitudesmentioning
confidence: 99%
“…They include elements such as explicit phonetics instruction, feedback, and oral practice with recording individual words, sentences, tongue twisters, or more extemporaneous speech (Correa & Grim, 2014;Ducate & Lomicka, 2009;Lord, 2008). Some researchers have suggested that such projects can improve learner attitudes toward pronunciation (Lord, 2008) or, when assigned as groupwork, create a sense of community among learners while fostering language learning (Lord & Harrington, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that certain types of pronunciation training may be more effective than others. For example, some studies relying on traditional pronunciation training (i.e., listening and repeating) indicate that the training may not have a significant effect on learners’ production of individual speech sounds (e.g., Lord, ). Training that relies primarily on accurate perception, however, has demonstrated its effectiveness (e.g., Gonzales‐Bueno & Quintana‐Lara, ).…”
Section: Teaching Stress Assignment Rulesmentioning
confidence: 99%
“…In language acquisition, phonological processing is also important because, to the extent it can be observed, it allows researchers to understand learners' real-time use of L2 phonological knowledge during comprehension of natural speech in the target language. Many studies on L2 phonology have examined learners' perception and production of L2 phones, which represent the product of L2 phonological knowledge (e.g., Baker & Trofimovich, 2006;Best & Tyler, 2007;Derwing & Munro, 2015;Díaz-Campos, 2004;Flege, 1995;Lord & Harrington, 2013;Saito et al, 2016). Few studies to date, however, have investigated learners' use of L2 phonological knowledge in real time, which represents the process of L2 phonological knowledge.…”
mentioning
confidence: 99%